Principles of salmonid culture - Pennell, William; Barton, Bruce A. (Developments in aquaculture and fisheries, 1996)
As salmonids have been reared for more than a century in many countries, one might expect that principles are well established and provide a solid foundation for salmonid aquaculture. Indeed, some of the methods used today in salmonid rearing are nearly identical to those employed one hundred years ago. Areas of salmonid research today include nutrition, smolt and stress physiology, genetics and biotechnology. The purpose of this book is to provide a useful synthesis of the biology and culture of salmonid fishes. The important practices in salmonid culture as well as the theory behind them is described. This volume will be of interest to students, researchers, fisheries biologists and managers as well as practising aquaculturists.